Handbook of Forensic Toxicology for Medical Examiners - Molina, M.D., D. K.; Hargrove, Veronica; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
Forensic professionals, particularly medical examiners$1 (Boften working through heavy caseloads$1 (Brequire quick and easy access to reliable sources of information to help interpret toxicology results. While several in-depth resources are available, they are often large, cumbersome, and contain more information than is often needed. The$1!# (BHandbook of Forensic Toxicology for Medical Examiners$1!# (Bis a concise handbook referencing the most common toxic substances and their reported non-toxic, toxic, and lethal concentrations, making it an ideal text for quick reference in the lab or autopsy room. Features of the Second Edition: Explains the principles of postmortem toxicology and the factors which must be considered Provides tables of toxicologic data for over 200 commonly encountered substances, including drugs of abuse, poisons, prescription drugs, and over-the-counter medications Includes discussion and description of the novel psychoactive drugs$1 (Bincluding synthetic opioids, cannabinoids, stimulants and hallucinogens Supplemental appendices provide additional information regarding specimen types and selection, testing methodologies, normal laboratory values, and conversion charts. The busy forensic professional needs a concise handbook that provides critical information quickly and accurately. This heavily referenced text offers an easy-to-use format allowing for rapid access for both routine daily use and preparation for courtroom testimony.s
List of Abbreviations -- 1. How to Use This Book -- 2. Special Drug Groups -- 3. Specific Drugs (Alphabetical Listing) -- Appendix A. Specimen Types and Collection -- Appendix B. Common Methodologies -- Appendix C. Normal Values Reference Charts -- Appendix D. Conversion Chart
Includes bibliographical references and index.
Also available in print format.
Keywords: Forensic toxicology -- Handbooks, manuals, etc; Medical examiners (Law) -- Handbooks, manuals, etc; Forensic toxicology; Medical examiners (Law); MEDICAL / Forensic Medicine; LAW / Forensic Science; forensic science; poisons; Electronic books